PASAT performance and the pattern of uptake of 99mTc-exametazime in brain estimated with single photon emission tomography. - Deary, I; Ebmeier, K; MacLeod, K; Dougall, N; Hepburn, D; Frier, B; Goodwin, G (1994)
The effect of the paced auditory serial addition test (PASAT) on the regional uptake of 99mTc-exametazime was determined by single photon emission computed tomography. Twenty insulin-treated diabetic outpatients were scanned at rest and during the performance of the PASAT task using split-dose injection of tracer. When resting and activation scans were compared there were significant decreases in tracer uptake in the right anterior cingulate and left posterior cingulate areas during PASAT activation. The findings are compared with previous studies which had implicated the anterior cingulate area in the mechanisms of attention in humans and other animals. The potentially confounding role of anxiety during attentional tasks is discussed.